Student satisfaction on thesis advising received in a Health School, Perú - Mamani-Benito, Oscar Javier (2021)
Objective: To determine the degree of satisfaction with the thesis advising received by graduates of a Health School, Peru. Material and methods: Analytical cross-sectional study conducted in 87 graduates, 15 of medicine, 22 of nursing, 19 of nutrition and 31 of psychology, who completed their thesis process during 2019. Data collection was carried out by means of a questionnaire of perception of satisfaction with respect to thesis advising, with prior informed consent. Results: 86.2 % were predominantly dissatisfied with the work of whoever was their advisor, 83 % did not define him/her as a researcher, 93 % felt that he/she did not have scientific publications, 93 % that he/she was not motivated to publish the results of his/her thesis and 83 % that he/she did not receive support with the paperwork. Conclusions: The degree of satisfaction of the students about thesis advising was unfavorable; advisors do not demonstrate scientific production and neither do they motivate to publish research results.